Pendidik dan upaya manajemen formulasi lembaga pendidikan Islam yang kreatif menghadapi masa pandemi covid-19 - Siti Makhmudah (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2021)
AbstracThis research shows several activities carried out in the home, working from home and studying from home. Learning from home is called online (learning with online sites). The design and application of long-distance learning literacy with the topic of Corona Virus 2019 Covid-19 aims to avoid this pandemic which is currently spreading completely and is very deadly. With this pandemic, it has not made the world of education lack sense in developing learning in the world of education at the RA, SD, SMP, SMA and Higher Education levels as well as Ponpes. Especially for students / learners who are still using via online as an intermediary for connecting their knowledge, while still minimizing the obstacles that occur during the online period. Therefore this discussion will be interesting. (1) the obstacles faced by students / learners, (2) the efforts made by the teachers / teachers / lecturers / educators, (3) the solutions made by the students / students and the teachers / teachers / lecturers / educators. This research uses a case study method and the research approach uses a qualitative case study method which is used to obtain information on the online learning process at the level of students who are still active in the world of higher education and Islamic boarding schools. The aim of the research is to find out to what extent, since the existence of Covid-19, all economies in the first world have collapsed as well as the world of education, including universities and boarding schools. The online school system will be implemented starting in the month of 2020. Not only in Indonesia but throughout the world. The correct formulation in this title is based on the formulation and composition in the right form in the form of the impact that occurs on students / students and teachers / teachers / lecturers / educators during the Covid-19 pandemic.Key words: Lecture Formulation, Creative Lectures, Covid Pandemic -19